Non cooperative household demand - Valérie Lechene; Ian Preston (Institute for Fiscal Studies (IFS), 2010)
We study non cooperative household models with two agents and several voluntarily contributed public goods, deriving the counterpart to the Slutsky matrix and demonstrating the nature of the deviation of its properties from those of a true Slutsky matrix in the unitary model. We provide results characterising both cases in which there are and are not jointly contributed public goods. Demand properties are contrasted with those for collective models and conclusions drawn regarding the possibility of empirically testing the collective model against non cooperative alternatives and the non cooperative model against a general alternative.
Keywords: D11; C72; 330; Nash equilibrium; Intra-household allocation; Slutsky symmetry; Privater Haushalt; Nachfrage; Öffentliches Gut; Nash-Gleichgewicht